2010
DOI: 10.1155/2011/765143
|View full text |Cite
|
Sign up to set email alerts
|

EDDK: Energy-Efficient Distributed Deterministic Key Management for Wireless Sensor Networks

Abstract: Energy efficiency is an essential requirement for wireless sensor networks while security must also be ensured for mission-critical applications. In this paper, we present an energy-efficient distributed deterministic key management scheme (EDDK) for resourceconstrained wireless sensor networks. EDDK mainly focuses on the establishment and maintenance of the pairwise keys as well as the local cluster keys and can fix some flaws in some existing key management schemes. Not only can the neighbor table constructe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 29 publications
1
37
0
Order By: Relevance
“…Analysis showed that their method had an extremely low overhead in terms of computation, communication, and storage. Wei et al (2010) [5] presented an energy-efficient distributed deterministic key management method (EDDK) for resource-constrained wireless sensor networks. EDDK generally focuses on the establishment and safeguarding of the pair-wise keys as well as the local cluster keys and can repair some flaws in some existing key management methods.…”
Section: ) Processor Power Managementmentioning
confidence: 99%
“…Analysis showed that their method had an extremely low overhead in terms of computation, communication, and storage. Wei et al (2010) [5] presented an energy-efficient distributed deterministic key management method (EDDK) for resource-constrained wireless sensor networks. EDDK generally focuses on the establishment and safeguarding of the pair-wise keys as well as the local cluster keys and can repair some flaws in some existing key management methods.…”
Section: ) Processor Power Managementmentioning
confidence: 99%
“…Thus symmetric key encryption is not appropriate for dynamic WSNs. All the more as of late, awry key based approaches have been proposed for dynamic , [10], [15]. These methodologies exploit of public key cryptography (PKC, for example, elliptic bend cryptography (ECC) or Identity based public key cryptography (ID-PKC) so as to streamline key foundation and information validation between hubs.…”
Section: Imentioning
confidence: 99%
“…Base station will transmit function identifier and random number, encrypted with individual key to individual nodes as shown in equation (3).…”
Section: Key Establishment Phasementioning
confidence: 99%